Evaluation of The Medical Board Exam in Portugal - Reis Marques*, Tiago (2018)
Introduction: There is a high heterogeneity in the structure of postgraduate medical training evaluation worldwide. However, in contrast to other countries, there have been no scientific studies of the final medical board examination, in Portugal. The present study aimed to evaluate the adequacy of the medical board examination including its validity as measured by its association with medical school grade average and national seriation examination.Material and Methods: Cross-sectional, observational study. We analyzed the final results on the medical board examination of 2439 physicians, across 47 specialties, who completed their training in 2016 and 2017, using measures of central tendency and variability. We assessed the association between these grades and the national exam to initiate residency, and the grade average in Medical School.Results: Measures of central tendency and variability, and consequent shape measures, revealed that the distribution of the scores of the final medical board exam is extremely negatively asymmetric and leptokurtic. A positive association was also found between the results in this exam and the score on national exam to initiate residency, and the grade average in Medical School.Conclusion: Although the medical board examination was, in general, positively associated with scores on the national exam to initiate residency, and the mean final Medical School grades, thus indicating its potential validity, our results demonstrate that this exam presents no satisfactory discriminative capacity. Therefore, there is room to improve the actual postgraduate medical examination model, including changes in its classification system and potentially consider other assessment models.